Is the current public health message on UV exposure correct? - Robyn M Lucas; Mike H Repacholi; Anthony J McMichael
Current sun safety messages stress the importance of sun protection in avoiding the consequences of excessive exposure to ultraviolet radiation (UVR), such as skin cancers, cataracts and other eye diseases, and viral infections caused by UV-induced immunosuppression. However, adequate exposure to UVR has an important role in human health, primarily through UV-induced production of vitamin D, a hormone essential to bone health. Vitamin D insufficiency may be associated with increased risks of some cancers, autoimmune diseases and mental health disorders such as schizophrenia. Here, we review the evolution of current sun exposure practices and sun-safe messages and consider not only the benefits, but also the detrimental effects that such messages may have. UVR-induced vitamin D production can be inhibited by factors such as deep skin pigmentation, indoor lifestyles, older age, sun avoidance behaviours and clothing habits that limit skin exposure, with deleterious consequences for health. There is some early evidence that sun-safe messages are beginning to cause a decrease in skin cancer rates in young people. After the widespread promotion of sun safety, it may now be appropriate to refine public health messages to take better account of variations between groups and their susceptibility to the dangers and benefits of sun exposure.